Trend analysis using mann-kendall, sen's slope estimator test and innovative trend analysis method in Yangtze river basin, china: review - Othman. Ali, Rawshan; Rashid Abubaker, Shadan (International Journal of Engineering and Technology, 2019)
Trend analysis of mean monthly flows is fundamental for better water resources management and planning in this study, Mann Kendall (MK), Sen's Method and Åžen's Innovative trend method (ITM) were utilized so as to analyze the possible trends of annual and seasonal flows. In this study, trends of flow of the Yangtze River were reviewed on in seasonal and annual time series utilizing the Mann-Kendall (MK) test, Sen's slope estimator, and innovative trend method (ITM). That is why, the monthly flow information will gather in the stations of Yangtze River Basin. In any case, the seasonal and annual warming magnitudes showed large regional differences, and a higher warming rate was identified in the eastern YRB and the western source area of the Yangtze River on the Qinghai-Tibetan Plateau (QTP). In general, a warming wetting trend was identified in the south-eastern and north-western YRB, while there was a warming-drying trend in a middle region. The developed maps of spatial variability of flow trends may help the stakeholders and/or water resource managers to figure out the risk and vulnerability related to climate change in the study region.Â Â Â